POTENSI DAYA TARIK EKOWISATA MANGROVE DI DESA KARANGSONG, KABUPATEN INDRAMAYU - Mayda Susana; Cecep Kusmana; Hadi Susilo Arifin (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2020)
The mangrove ecosystem in Karangsong is an area that has apotential to attract ecotourism which can be developed and enjoyed as an ecotourism area. This study aims to analyze the potential attractiveness of ecotourism by using the method of observation and interviews. The analysis used isAnalysis of the OperatingArea-Objectsand Natural Tourist Attractions (ADO-ODTWA) developed bythe Directorate General of Forest Protection and Nature Conservation in2003. The results showed that potential objects for ODTWA in the Karangsong mangrove area whichreceived high scores arethe attraction of mangrove tourism objects, market potential, management and services, accommodation, supporting facilities and infrastructure, relationships with surrounding tourism objects, security, carrying capacity of the area, visitor arrangements, marketing,and market share.The potential objects that getmoderate value are the level of relationship/accessibility, climate,availability of clean water, and condition of the surrounding area. The feasibility value of developing natural tourist attraction objects in the Karangsong mangrove area has a high classification of 6,565, the potential is leisure activities to enjoy flora, fauna, photo hunting activities, educational and research activities, and boating activities.